The night of Baba Yaga - Ōtani, Akira, 1981- (Soho Crime, 2024)
"Tokyo, 1979. Yoriko Shindo, a workhorse of a woman who has been an outcast her whole life, is kidnapped and dragged to the lair of the Naiki-kai, a branch of the yakuza. After she savagely fends off a throng of henchmen in an attempt to escape, Shindo is only permitted to live under one condition: that she will become the bodyguard and driver for Shoko Naiki, the obsessively sheltered daughter of the gang's boss. Eighteen-year-old Shoko, pretty and silent as a doll, has no friends, wears strangely old-fashioned clothes, and is completely naive in all matters of life. Originally disdaining her ward, Shindo soon finds herself far more invested in Shoko's well-being than she ever expected. But every man around them is bloodthirsty and trigger-happy. Shindo doubts she and Shoko will survive much longer if nothing changes. Could there ever be a different life for two women like them? Akira Otani's English-language debut moves boldly through time and across gender, stretching the definitions and possibilities of each concept. Rendered in a gorgeous translation by International Booker-shortlisted Sam Bett, this lean, mean thriller proves that bonds forged in fire are unbreakable"--